Parents' school‐related concerns and perceived strengths in youth with spina bifida. (2nd February 2022) - Winning, Adrien M.; Ridosh, Monique; Wartman, Elicia; Kritikos, Tessa; Friedman, Catherine; Starnes, Meredith; Crowe, Autumn N.; Holmbeck, Grayson N.
Abstract: Background: Although the academic difficulties of children with spina bifida (SB) are well‐documented, there is limited literature on parents' views of their children's school experiences and school‐related supportive services. Thus, the current study examined parents' school‐related concerns, as well as perceived areas of strength, among children with SB. Methods: Using a mixed‐methods approach, 30 families (29 mothers and 19 fathers) of children with SB (ages 8–15 years) completed questionnaires and interviews. Content analysis was used to generate themes from interview data about parents' school‐related concerns and perceptions of their child's strengths. Results: Overall, six themes emerged when assessing both parents' concerns and perceived strengths. Some parents did not endorse school concerns or strengths for their child. However, other parents described concerns related to academic performance, cognitive abilities, lack of school support, missed school and/or class time and disengagement, as well as strengths such as academic skills, cognitive abilities, persistence, self‐advocacy and agreeableness. Despite parents' concerns about their children's academic performance, quantitative data revealed that less than 50% of children had received a neuropsychological evaluation and/or academic accommodations; additional quantitative data supported the qualitative findings. Conclusions: The mixed‐methods approach used in this study provides a richer understanding of parents' experiences in the school setting when they have a child with SB. Results can inform clinical practice, identifying a need to improve academic support for children with SB and help parents manage education‐related stressors.